MEDIASI PENAL SEBAGAI KEBIJAKAN HUKUM PIDANA DALAM PENYELESAIAN TINDAK PIDANA LALU LINTAS YANG MENYEBABKAN KERUGIAN MATERIL DI POLRESTABES MAKASSAR - Hamka Mappaita (Universitas Islam Negeri Alauddin, 2019)
The research was carried out and aimed at: 1) to find out the application of reasoning mediation as a criminal law policy in resolving traffic crimes which caused material losses at the Makassar Police Precincts; 2) To find out and analyze what factors are the inhibitors of the Makassar Polrestabes Satlantas Investigator in applying reasoning mediation as a criminal law policy in resolving traffic crimes that cause material losses at the Makassar Polrestabes.This type of research is empirical legal research, namely legal research that examines the implementation or implementation of positive legal provisions (legislation) factually on any particular legal event that occurs in society. The legal material used consists of primary legal data and secondary legal data. Techniques for collecting legal data are collected through literature studies and field studies. Then the technique for analyzing with qualitative analysis techniques by sorting and selecting, classifying, and connecting the realities that occur in the field with the problems studied, so as to provide a clear picture of what happened in the field so that it comes to a conclusion.The results of the study show that: 1) The application of penal mediation by the Makassar Tabes Regional Police Satlantas investigator to a traffic accident that caused material losses at the Makassar Polrestabes has been running optimally; 2) The inhibiting factor in the application of reason mediation in Makassar Polrestabes is internal factors, namely legal factors that have not explicitly regulated the settlement of traffic accidents which cause material losses, the investigator's resource factors are still lacking when compared to the number of cases handled. External factors are people who sometimes do not want peace or requests from the victims or the families of victims who request compensation that is too large so the perpetrators cannot.Â